Treatment and outcome of Ganglioneuroma and Ganglioneuroblastoma intermixed. Issue 1 (December 2016) - Decarolis, Boris; Simon, Thorsten; Krug, Barbara; Leuschner, Ivo; Vokuhl, Christian; Kaatsch, Peter; von Schweinitz, Dietrich; Klingebiel, Thomas; Mueller, Ingo; Schweigerer, Lothar; Berthold, Frank; Hero, Barbara
Abstract Background Ganglioneuroma (GN) and ganglioneuroblastoma intermixed (GNBI) are mature variants of neuroblastic tumors (NT). It is still discussed whether incomplete resection of GN/GNBI impairs the outcome of patients. Methods Clinical characteristics and outcome of localized GN/GNBI were retrospectively compared to localized neuroblastoma (NB) and ganglioneuroblastoma-nodular (GNBN) registered in the German neuroblastoma trials between 2000 and 2010. Results Of 808 consecutive localized NT, 162 (20 %) were classified as GN and 55 (7 %) as GNBI. GN/GNBI patients presented more often with stage 1 disease (68 % vs. 37 %, p < 0.001), less frequently with adrenal tumors (31 % vs. 43 %, p = 0.001) and positive mIBG-uptake (34 % vs. 90 %, p < 0.001), and had less often elevated urine catecholamine metabolites (homovanillic acid 39 % vs. 62 %, p < 0.001, vanillylmandelic acid 27 % vs. 64 %, p < 0.001). Median age at diagnosis increased with grade of differentiation (NB/GNBN: 9; GNBI: 61; GN-maturing: 71; GN-mature: 125 months, p < 0.001). Complete tumor resection was achieved at diagnosis in 70 % of 162 GN and 67 % of 55 GNBI, and after 4 to 32 months of observation in 4 GN (2 %) and 5 GNBI (9 %). Eleven patients received chemotherapy without substantial effect. Fifty-five residual tumors (42 GN, 13 GNBI) are currently under observation (median: 44 months). Five patients (3 GN, 2 GNBI) showed local progression; all had tumor residuals > 2 cm. No progression occurred after subtotal resection. Two patients died of treatment, none of tumor progression. Conclusions GN/GNBI account for one quarter of localized NT and differ from immature tumors in their clinical features. Chemotherapy is not effective. Subtotal resection appears to be a sufficient treatment. Trial registration ClinicalTrials.gov identifiers - NB97 (NCT00017225; registered June 6, 2001); NB2004 (NCT00410631; registered December 11, 2006)